Comparative study of the mesio-distal size between homologous teeth in permanent dentition - Carhuamaca León, Gregorio Javier (2013)
The objective of the present study was to determine the difference mesiodistal crown between the homologous teeth in the permanent dentition and to establish the relation of the mesiodistal size, according to the gender. For this purpose, there were 120 study models that belonged to 120 students (60 boys and 60 girls) between 12 – 18 years old of 5 Educational Institutions in Chaclacayo (Lima – Peru) according to the inclusive and exclusive criteria; the mesio-distal sizes of the teeth were measured in each model. It was used a Centesimal Vernier with 0,02 mm of precision. The collected data was analyzed with the “t” of Student for determine the significant difference. Results: There was significant the discrepancy in the mesiodistal diameter. For men in 7 homologous teeth (Maxilla: lateral incisors, canines and second bicuspids; Mandible: central incisor, lateral incisors, canines and first molars) and for Women in 4 homologous teeth (Maxilla: central incisor, canines, first bicuspids; Mandible: second bicuspid). It was concluded that there is a significative mesiodistal discrepancy between homologous teeth (7 teeth in men and 4 teeth in women). Also the sexual dimorphism was confirmed, the mesiodistal diameter in men were greater than women.